Valuing the “Burden” and Impact of Rare Diseases: A Scoping Review - Delaye, Julien; Cacciatore, Pasquale; Kole, Anna (Frontiers in Pharmacology, 2022)
Introduction. Rare diseases (RDs) are a severe, chronic, degenerative and often life-threatening group of conditions affecting more than 30 million people in Europe. Their impact is often underreported and ranges from psychological and physical symptoms seriously compromising quality of life. There is then a need to consolidate knowledge on the economic, social, and quality of life impacts of rare diseases. Methods. This scoping review is the result of 9 qualitative interviews with experts and a literature search on Cost-of-Illness (COI) studies and quality of life (QoL) studies following the PRISMA methodology. Grey literature was also included to complement findings. Results. 63 COI studies were retrieved, covering 42 diseases and a vast majority of them using a prevalence-based approach (94%). All studies included medical costs, while 60% included non-medical costs, 68% productivity losses and 43% informal care costs. 56 studies on QoL were retrieved, mostly from Europe, with 30 different measurement tools. Grey literature included surveys from the pharmaceutical industry and patient organisations. Discussion. The majority of studies evaluating the impact of RDs on the individual and society use the COI approach, mostly from a societal perspective. Studies often vary in scope, making them difficult to consolidate or compare results. While medical costs and productivity losses are consistently included, QoL aspects are rarely considered in COI and are usually measured through generic tools. Conclusion. A comprehensive study on impact of rare disease across countries in Europe is lacking. Existing studies are heterogeneous in their scope and methodology and often lack a holistic picture of the impact of rare. Consensus on standards and methodology across countries and diseases is then needed. Studies that consider a holistic approach are often conducted by pharmaceutical companies and patient organisations exploring a specific disease area but are not necessarily visible in the literature and could benefit from the sharing of standards and best practices.